Profiling bilingualism in an historically Afrikaans community on the Beaufort West Hooyvlakte - Anthonie, Alexa N. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (General Linguistics))--University of Stellenbosch, 2009.